Comparison Postoperative Shoulder Pain, Nausea, and Vomiting Between Low and Normal Pressure Pneumoperitoneum in Laparoscopic Cholecystectomy - Nematihonar, Behzad; Fahimihanzaei, Hosein; Kamranmanesh, Mohammadreza; Memary, Elham; Shahbazi, Arash; Mirkheshti, Alireza (Annals of Anesthesiology and Critical Care, 2017)
Background: Low-pressure pneumoperitoneum during laparoscopic surgeries decreases some side effects related to inflate gas into abdominal cavity. The current study aimed at comparing the effects of standard- and low-pressure pneumoperitoneum on shoulder pain, nausea, and vomiting after laparoscopic cholecystectomy. Methods: In a randomized clinical trial, 202 ASA classes I and II patients, candidates for elective laparoscopic cholecystectomy, were randomly divided into the groups of standard- (12 to 14mmHg)and low- (6 to 7mmHg)pressure pneumoperitoneum. Postoperative shoulder pain, nausea, and vomiting were assessed between the 2 groups. Results: Post-operative shoulder pain was statistically lower in low-pressure group in comparison with standard-pressure group (P = 0.001). Nausea and vomiting were not statistically different between the 2 groups (P = 0.54). Conclusions: Low-pressure pneumoperitoneum during laparoscopic cholecystectomy was an efficient method to decrease postoperative shoulder pain